CLINICAL AND LABORATORY FEATURES OF THYMOMEGALY IN YOUNG CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Thymomegaly - hyperplasia of the thymus and its hypofunction, accompanying a number of diseases of childhood. Minor thymomegaly is asymptomatic; pronounced thymus enlargement may manifest with vital organ compression syndrome, lymphoproliferation syndrome, immune and endocrine-exchange disorders [6,7,8,9].